2015
DOI: 10.1177/0022167815621647
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Growth During Incarceration: A Case Study From an Experiential–Existential Perspective

Abstract: Life after a traumatic experience is never easy. This is certainly the case for victims. For many offenders, committing a crime might be a traumatic experience as well, and incarceration may confront them even more with the consequences of their deeds. Humanistic therapies are very suitable for encouraging clients to embark on an explicit meaning-making process. In this article, we explore with a case study how experiential-existential therapy can foster meaning making and posttraumatic growth in prisoners. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…More recently, researchers have explored how experiential-existential therapy can be used with prisoners. Utilizing a case study application, Vanhooren, Leigssen, and Dezutter (2018) explored how this mode of therapy can “foster meaning making and posttraumatic growth in prisoners” (p. 144).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…More recently, researchers have explored how experiential-existential therapy can be used with prisoners. Utilizing a case study application, Vanhooren, Leigssen, and Dezutter (2018) explored how this mode of therapy can “foster meaning making and posttraumatic growth in prisoners” (p. 144).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…EFT has been shown to be effective in addressing the underlying and dysfunctional processes for many psychological problems and disorders: depression (Watson, Gordon, Stermac, Kalogerakos, & Steckley, 2003), anxiety (Watson & Greenberg, 2017), and complex trauma (Paivio & Pascual-Leone, 2010). Although experiential approaches and EFT have been integrated in forensic practice (Gunst, 2012; Vanhooren, Leijssen, & Dezutter, 2018), there is little research evaluating its effectiveness. One study (Pascual-Leone, Bierman, Arnold, & Stasiak, 2011) found that participants abstained longer from violent reoffenses.…”
Section: Eftmentioning
confidence: 99%
“…Being listened to by others helps a person work through the emotional elements of the distressing event and to create new narratives and meanings (Tedeschi & Calhoun, 2004). In the qualitative studies on posttraumatic growth, the experience of a therapeutic relationship was found to be highly corrective and transformative for offenders (Ferrito et al, 2012;Mapham & Hefferon, 2012;van Ginneken, 2016;Vanhooren et al, 2015Vanhooren et al, , 2017b This experience helped them find new ways to connect with themselves, with people outside the therapy, and led to posttraumatic growth.…”
Section: Posttraumatic Growth and The Role Of Coping Strategiesmentioning
confidence: 99%
“…Recently, qualitative studies have described posttraumatic growth as a profound shift in how offenders and prisoners experience themselves, the others, and the world as a result of processing a loss of meaning induced by crime and imprisonment (Elisha et al, 2013;Ferrito et al, 2012;Guse & Hudson, 2014;Mapham & Hefferon, 2012;van Ginneken, 2016;Vanhooren et al, 2015;Leijssen & Dezutter, 2017b). Similar to the general population, these qualitative studies found strategies such as emotional coping, religious coping, and searching for meaning to be supportive of the process that leads to posttraumatic growth.…”
Section: Aim Of the Studymentioning
confidence: 99%